Mengidentifikasi Miskonsepsi Fluida Statis pada Mahasiswa Calon Guru Fisika Universitas samudra - Kanadhien Zukhruf (Program Studi Pendidikan Fisika FKIP Universitas Samudra, 2018)
Abstrcat This study is intended to obtain a profile of misconceptions of students of the langsa oceanic physics teacher candidates in statistical fluid material where misconceptions are experienced by prospective physics teacher students. The population of this study was prospective physics teacher students. The method used in this research is descriptive method. The sampling technique uses purposive sampling technique. As for the sample in the study were fifth-semester students who were healthy 19 people, consisting of 3 men and 16 women. Data collection was carried out with the tests selected as many as 20 items that were completed with a matrix of the three-tier test results. Processing and analysis of data using Excel. Through this research, it is known that the level of misconception of students of physics teacher candidates at the University of Samudra is 53%. Based on the results of the analysis of the problem the biggest misconception about number 5 is 78%, because students cannot find errors and mistakes made by wrong intuition, and also not careful the concept of mass meetings. In addition, gifted students who have good concepts are 11%. Keywords: Misconception, statistical fluid, three-tier test.